Dual Reinforcement Q Routing for Ad Hoc Networks - Rahul M Desai; B P Patil (Institute of Advanced Engineering and Science, 2017)
Ad Hoc Networks are infrastructure less network in which nodes are connected by Multi-hop wireless links. Each node is acting as a router as it supports distributed routing. Routing challenges occurs as there are frequent path breaks due to the mobility. Various application domains include military applications, emergency search and rescue operations and collaborative computing. The existing protocols used are divided into proactive and on demand routing protocols. The various new routing algorithms are also designed to optimize the performance of a network in terms of various performance parameters. Dual reinforcement routing is learning based approach used for routing. This paper describes the implementation, mathematical evaluation and judging the performance of a network and analyze it to find the performance of a network.